2019
DOI: 10.1016/j.drudis.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic peptides: types, synthesis and applications

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Here, peptide therapy has emerged as a viable treatment option for solid tumors, especially breast cancer. Peptides are attractive treatments because of their precise attachment to the surface of tumor cells, low molecular weight, and low toxicity to normal cells [ 37 , 38 ].…”
Section: Peptide-based Strategies For Targeted Breast Cancermentioning
confidence: 99%
“…Here, peptide therapy has emerged as a viable treatment option for solid tumors, especially breast cancer. Peptides are attractive treatments because of their precise attachment to the surface of tumor cells, low molecular weight, and low toxicity to normal cells [ 37 , 38 ].…”
Section: Peptide-based Strategies For Targeted Breast Cancermentioning
confidence: 99%
“…[ 29 ] Considering the biopotential of natural cyclooligopeptides including bicyclic peptides, these bioactive metabolites are synthesized in the laboratory by various research groups. [ 14,30–37 ] Bioactive bicyclic peptides are obtained from lithistid sponge Aciculites orientalis and Theonella sp., including Red Sea sponge Theonella swinhoei . Aciculitins A–C ( 15 – 17 ), theonellamides A–G ( 18 – 24 ), theonegramide ( 25 ), theopalauamide ( 26 ), and isotheopalauamide ( 27 ) are the best examples of bicyclic peptides from marine sponges.…”
Section: Bioactive Bridged Macrobicyclic Peptides From Marine Spongesmentioning
confidence: 99%
“…In addition, each ring in the bicyclic structure can function independently, allowing these peptides to be bifunctional. [ 6,14 ]…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective ways to increase the stability of peptides is the synthesis of cyclic peptides. These peptides are resistant to exonucleases due to the lack of N-terminals and C-terminals, and it has also been found that their circular shape and specific conformation are more efficient in terms of Gibbs free energy for bonding with targets [ 27 ]. Modifications to one of the epidermal growth factor receptor (EGFR) domains and cyclic peptide production, for example, were used to create a cytotoxic state for cancer cells [ 28 ].…”
Section: Introductionmentioning
confidence: 99%